Effect of roll angle configurations of a reverse delta type add-on device on wing tip vortex alleviation - Altaf, Afaq; Mohammed Aldheeb, Mohammed Abdulmalek; Omar, Ashraf Ali; Asrar, Waqar (Semarak Ilmu Publishing, 2024)
An add-on device in the shape of a reverse delta has shown the ability to alleviate wake vortices. The present work studies the interaction of the wing tip vortex and the reverse delta type add-on device vortices. This paper looks at the vortex interactions generated downstream of the wing tip in planes perpendicular to the free stream direction and their dependence on roll angles φ at a mean chord-based Reynolds number of Rec=2.75×105. The study reveals that the add-on device causes a reduction in the tangential velocity V and vorticity of the resultant vortex by up to 44.1% and 59.4%, respectively. Also, it is found that the resultant vortex core radius increased by 305%. The results indicate that the reverse delta type add-on device implants countersign vorticity into the wing tip vortex and modifies its roll-up process.